Anesthetic Care of the Pregnant Patient With Cardiovascular Disease: A Scientific Statement From the American Heart Association. Issue 11 (13th February 2023) - Meng, Marie-Louise; Arendt, Katherine W.; Banayan, Jennifer M.; Bradley, Elisa A.; Vaught, Arthur J.; Hameed, Afshan B.; Harris, Jade; Bryner, Benjamin; Mehta, Laxmi S.; ,
Abstract : The pregnancy-related mortality rate in the United States is excessively high. The American Heart Association is dedicated to fighting heart disease and recognizes that cardiovascular disease, preexisting or acquired during pregnancy, is the leading cause of maternal mortality in the United States. Comprehensive scientific statements from cardiology and obstetrics experts guide the treatment of cardio-obstetric patients before, during, and after pregnancy. This scientific statement aims to highlight the role of specialized cardio-obstetric anesthesiology care, presenting a systematic approach to the care of these patients from the anesthesiology perspective. The anesthesiologist is a critical part of the pregnancy heart team as the perioperative physician who is trained to prevent or promptly recognize and treat patients with peripartum cardiovascular decompensation. Maternal morbidity is attenuated with expert anesthesiology peripartum care, which includes the management of neuraxial anesthesia, inotrope and vasopressor support, transthoracic echocardiography, optimization of delivery location, and consideration of advanced critical care and mechanical support when needed. Standardizing the anesthesiology approach to patients with high peripartum cardiovascular risk and ensuring that cardio-obstetrics patients have access to the appropriate care team, facilities, and advanced cardiovascular therapies will contribute to improving peripartum morbidity and mortality.